SCHOOL LEADERSHIP, INSPECTION AND VISIBILITY: PANOPTICISM AND POST-PANOPTICISM IN AN ENGLISH COASTAL AREA OF DEPRIVATION. Issue 1 (2nd January 2022) - Colman, Aly
ABSTRACT: This paper contributes to recent debates pertaining to neoliberal technologies of performativity including fabrication, panopticism and post-panopticism. These terms are discussed here in relation to constant visibility from recent school inspection arrangements in England and the impact of this on school leadership. Case study research within one seaside town was drawn from two schools, one, a state primary school and the other, a state secondary school, located within an area of deprivation. Both schools had been judged as requires improvement by Ofsted, but immediately before the fieldwork commenced, the secondary school received a judgment of good. Fourteen semi-structured interviews with thirteen leaders in a range of roles were undertaken to examine the conditions created by school inspection. Data is considered in relation to the features of panopticism and post-panopticism and shows leaders experience constant visibility, the pressures of performing to shifting expectations, and resultant staffing instability. This is not conducive to leaders working to improve schools, particularly those serving areas of deprivation.